ANALISIS STRATEGI DAN PENYUSUNAN LAPORAN KEUANGAN PADA BANK MINI: Studi Kasus di Bank Mini MI Plus Darul Hikmah Kalijaten-Taman-Sidoarjo - Virda Kurnia Sari (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
Mini bank is a means or place for students to save their money with an unspecified amount. This mini bank is not only a facility for students, but also teachers and education staff can save in this mini bank. Fund management gives a very influential contribution to the success of the implementation of education. Educational institutions are allowed to carry out financial self-management by referring to the standards set by the government. Therefore, educational institutions develop strategies in the development of financial administration management. The purpose of this study is to find out what strategies are used in mini banks and how to prepare financial reports. The method used in this research is to use a qualitative descriptive method. The results of this study indicate that the strategy chosen to promote the performance of mini-bank practices is very much needed, besides that the process of preparing financial reports still uses a manual system by recording them into a ledger. This was done because the mini bank at MI Plus Darul Hikmah had collaborated with Bank Syari'ah Indonesia (BSI), and the records were only used as evidence that students had saved their money in the mini bank